STUDY OF DYNAMICS OF SUSPENDED SEDIMENT CONCENTRATION IN TANARA WATERS BY UTILIZING LANDSAT IMAGERY - Suhanda, Delilla
Suspended sediment transport is one process that occurs in coastal areas, especially estuaries. This study aimed to examine the suspended sediment concentration condition spatially and temporally and form an empirical formula for measuring the concentration of suspended sediment using Landsat imagery data based on distance and river discharge parameters. The research location is in Tanara Waters, Serang Regency. Field data were collected at six stations on April 10, 2012. Sampling was carried out using a bottle sampler (Nansen bottle) directly at depths of 0.2d; 0.4d; and 0.8d. Field samples were processed using the SNI 03-3961-1995 method to determine the water's total weight of suspended sediment. Processing satellite image data using Landsat 7 and 8 was carried out with radiometric correction, atmospheric correction, and calculation of suspended sediment concentration. The measure of the suspended sediment concentration value is determined by applying the suspended sediment algorithm that has been developed by Budhiman (2004), Parwati (2006), and Jaelani (2016) to find out the results that are closest to the field data values of the three algorithms. The results of data processing and validation analysis using Root Mean Square Error (RMSE), Normalized Mean Absolute Error (NMAE), and Mean Absolute Error (MAE). Judging from the RMSE value between the field data and the three algorithms, the values are 16.85; 14.31; and 21.38. After modification of the algorithm developed by Budhiman (2004) the RMSE value became 9.24. Algorithm modification is applied to image data from 2002 – 2021. The distribution of suspended sediment concentration in Tanara Waters is dominantly influenced by river discharge. The concentration of suspended sediment is affected by distance. The farther offshore, the smaller the concentration of suspended sediment and forms an exponential relationship pattern. The form of equation measuring the concentration of suspended sediment is created using regression by reviewing the relationship between river discharge and distance (Q/L), resulting in the equation SS (mg/l) = 21.801+0.056 (Q/L). The resulting RMSE value was 5.20 mg/l.